Pioneers of Jewish Ethnography and Folkloristics in Eastern Europe - Bar-Itzhak, Haya (Studia Mythologica Slavica Supplementa, 2010)
The few scholarly treatments of Jewish ethnography and folklore studies in Eastern Europe have focused mostly on the collection of folklore materials. But even when Jewish folklore studies in Eastern Europe were still in their infancy, some scholars and authors made important contributions to the theoretical side of the discipline. This book focuses on these contributions and includes both discussion of these early folklorists and translations of some of their key writings. The pioneers of Jewish ethnography and folkloristics dealt with many areas and genres: folk narrative, folk songs, humor and jokes, beliefs and customs, folk medicine, folk art and material culture, and the interplay between folklore and history and between folklore and literature. Most of the research questions they posed continue to engage scholars today, and answers supplied by them remain relevant today and can serve as building blocks for the future.